Agrandamientos gingivales inducidos por drogas - Soto, Jorge; Naicipa, Mario (Revista Estomatología, 1995)
Some therapeutic Agents and drugs may induce changes in the periodontal tissues, specially he gingivae. They are classified as sistemic drugs, compounds that may be applied topically and heavy metals. Among the most commonly used sistemic drogs we can find Fenitoyn Nifedipins- Ciclosporin, sodium valproate wich gene rally produce gingival enlargement. This artice reviews farmacocinetics, involvement of periodontal tissue, pathogenesis, like sensitised fibroblast, to Fenitoyn, as well as clinical and histologic changes produced by these drugs. Treatment will also be discussed.